Pelaksanaan Supervisi Pengajaran Di Sekolah Menengah Atas - Wafiq Azizah; Andi Mappincara; Andi Nurochmah (Universitas Negeri Makassar, 2023)
The researcher's purpose is to determine how to implement teaching supervision in the school. This research approach is a qualitative approach with a descriptive type of research. The data sources in this study are principals, vice principals, and teachers—data collection techniques are in the form of observation, interviews, and documentation. Data analysis techniques use data collection, redaction, presentation, and conclusion. They check the validity of the data using triangulation techniques. The results showed that: 1) the implementation of teaching supervision using teaching supervision planning is carried out by holding a principal meeting with the team and teachers to determine the aspects assessed by making a schedule for the implementation of teaching supervision, using a directive, collaborative and non-directive approach, using unique techniques or class visits, as for the evaluation of learning carried out during the implementation of teaching supervision, namely seeing The presence of the teacher when teaching to students as well as photos at the time of learning as evidence that the teacher carries out the learning process. 2) obstacles faced in the implementation of teaching supervision, namely, the lack of teacher readiness regarding administration related to learning tools, feeling uncomfortable or unwell towards fellow teachers, and the lack of supporting facilities in the implementation of teaching supervision, such as learning media related to in focus.